Efek Ekstrak Etanol 70% Daun Kemangi Ocimum americanum L.) Terhadap Perbaikan Sel Spermatogenik Tikus Sprague-Dawley Jantan - Azrifitria Azrifitria; Eka Putri (UIN Syarif Hidayatullah Jakarta, 2023)
Kemangi is a strong aromatic herb with aphrodisiac activity. The content of secondary metabolites that are antioxidants in kemangi are thought to be able to overcome fertility disorders due to the work of free radicals. The aim of this study was to screen for phytochemicals and to analyze the activity of 70% ethanol extract of kemangi leaves (Ocimum americanum L.) on the repair of spermatogenic cells in male sprague-dawley rats exposed to lead. The results of phytochemical screening showed that the basil leaf extract was positive for alkaloids, flavonoids, tannins, and saponins. The results of administration of 70% ethanol extract of kemangi leaves at a dose of 50 mg/KgBW, 100 mg/KgBW, and 200 mg/KgBW in rats that had been induced by lead acetate increased the diameter of the seminiferous tubules, the number of pachytene cells, and round spermatid cells compared to the negative control but not significantly different (p > 0.05). The highest increase in all parameters of the spermatogenic cell repair test was given the kemangi leaves extract at a dose of 200 mg/KgBW.